PERDAGANGAN OPIUM DAN NARCOTERRORISM DI AFGHANISTAN (STUDI KASUS NARCOTERRORISM OLEH TALIBAN TAHUN 2007-2010) - Ines Setiana; Reni Windiani; Shary Charlotte Pattypelohy (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
The opium trafficking in Afghanistan is one of the international crimes that have long been a state problem. It becomes more complicated when terrorist organizations get involved. Hence narcoterrorism. Narcoterrorism has been existing in Afghanistan since the Taliban in charge. This research analyze about the Opium Trafficking and Narcoterrorism in Afghanistan (Study Case: Narcoterrorism by the Taliban in 2007-2010) by using the theory of rational choice. The research method is qualitative method. The research’s data was obtained from journal, book, and UNODC publication. The result of this research is Taliban are still involved with narcoterrorism. The Taliban interests is to obtaining funds to finance their activities. While the interest of poppy farmers is to get protection in order to keep doing opium cultivation. The Taliban’s action is collecting taxes and providing protection for opium farmers. In return, the farmers pay the taxes set by the Taliban.